Determinant genes that effect the central nervous system and their antenatal identification - Vijay, Christy; Tilak, Preetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The central nervous system is an intricate networking of electric signals that intertwines the functioning of all senses of speech, thoughts etc. A genetic mutation in this complex structure is known to cause many neurological diseases. Methods: Records of the genetic analysis reports of patients were studied. Patients with CNS genetic syndromes or tubulinopathies in fetus of the present pregnancy or previous pregnancy who presented themselves only for genetic counseling with the genetic analysis report done at an outside diagnostic center were selected. Results: Ten patients presented with history congenital abnormalities of the structure of the central nervous system in pregnancy. Non-invasive investigations in the first child led to the need for genetic analysis of the present foetus. EEG showing independent S2 foci and left central parietal and right temporal region with bilateral synchronous discharge was noticed. MRI findings such as chronic infarct with encephalomalacia were seen. Conclusions: Our study identified genes responsible for CNS abnormalities in structure and function and the Exom sequence in which they occurred. We were able to observe various types of clinical presentations of the syndromes on MRI/USG.